Pelatihan Pengelolaan Instagram Komunitas Desa Dieng sebagai Sarana Promosi Potensi Wilayah - Annis Azhar Suryaningtyas; Sika Nur Indah (Universitas Muhammadiyah Semarang, 2022)
Dieng Wetan Village is one of the areas in Wonosobo Regency that has tourism potential. In publicizing their tourism potential, local youth released an Instagram account @desadieng. However, the publication of tourism through this account is a problem. This is due to several factors. First, the lack of human resources (HR) from the youth organizations of Dieng Wetan Village as managers. Second, the need to strengthen HR skills in terms of content writing, photo and video production as a medium for publication of regional tourism potential. Therefore, it is necessary to carry out a training in the production of written and photo content for youth members of Dieng Wetan Village as the manager of the official @desadieng account as a form of publication of regional tourism potential. The training was carried out in four stages, including situation analysis, planning, implementation, and evaluation. The training program which was held for two days began with the provision of materials, discussions, field practices, and evaluations. As a result, participants were able to create promotional content for the tourism potential of Dieng Wetan Village through Instagram social media channels. In the future, participants need to sharpen their sensitivity to local wisdom issues that can enrich publication materials. In addition, public awareness also needs to be formed so that they can independently manage the @desadieng account as the official and consistent official account of Dieng Wetan Village tourism publications.